Fault tolerance of asymmetrical six-phase induction machine during single open circuit fault to three open circuit faults using GUI - Ungku Mohamed Ismail Adrian Ungku Abdul Rahman; Wan Noraishah Wan Abdul Munim; Hang Seng Che; Mahdi Tousizadeh; Khairul Safuan Muhammad (Institute of Advanced Engineering and Science, 2020)
The fault tolerance of multiphase drive is favourable in the industry for its reliability and safety reasons. However, from the educational point of view, the post-fault capability of six-phase machine is still unclear. This paper presents the fault tolerance of asymmetrical six-phase induction machine (A6-IM) under one to three open-circuit faults using Graphical User Interface (GUI). In this study, the capability of A6-IM has been interpreted through a simple and user-friendly GUI helping students to have a better understanding on the current limits of A6-IM. The optimization of post-fault current references is based on maximum torque (MT) and minimum loss (ML). This work provides GUI highlighting the post-fault derating of A6-IM with single isolated neutral (1N) in two different modes namely MT and ML for educational purposes.